Hubungan Tingkat Pengetahuan tentang DASH (Dietary Approaches to Stop Hypertension) dengan Tingkat Kepatuhan terhadap Diet: Studi Literatur - Wardani, Aulia Dwi; Sudaryanto, Agus (STIKES Ngesti Waluyo, 2023)
High blood pressure or hypertension is still a problem with quite high prevalence of morbidity and mortality. According to Indonesian Basic Health Research (Riskesdas) data, the prevalence of hypertension sufferers in 2013 was 25.8%, then increased in 2018 to 34.1% in the population aged ≥18 years. Blood pressure can be controlled by managing lifestyle and implementing a Dietary Approaches diet to Stop Hypertension (DASH). DASH is an eating plan to reduce or control high blood pressure that focuses on foods low in sodium as well as foods rich in magnesium, potassium, calcium, and other nutrients. This study aims to analyze the level of knowledge about DASH and the level of adherence to the diet. This research used the Literature Review method using narrative descriptive analysis. In searching for articles, the PRISMA method was used as a guidance to search through Google Scholar, Science Direct, and PubMed databases. The results of the literature review from 17 articles showed that knowledge about the DASH diet can be effectively obtained through WhatsApp group learning videos, audiovisual media (images and sound), family-based education, and nutritional counseling. Meanwhile, adherence to the diet can be increased through providing educational videos, DASH-like diet messages via WhatsApp, direct health education, mindfulness training programs, and applying the Transtheoretical model (TTM) method. A high level of knowledge about the DASH diet can increase adherence to the hypertension diet. In addition, knowledge about the DASH diet followed by increasing regular food consumption can increase compliance in following the diet.